Analisis Penempatan dan Penugasan Tenaga Kependidikan di SMP Negeri 18 Surabaya - Lazuardy, Dellast A’yunil; Untami, Dian Tri; Fatma, Arik Nabila; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (Lembaga Yasin AlSys, 2024)
This study aims to understand the process, strategies, and obstacles related to the placement and assignment of education personnel at SMPN 18 Surabaya. The method used is descriptive qualitative, involving the principal, head of administration as the main source of information, vice principal, and teaching staff as additional sources of information. Data were collected through observation, interviews, and document analysis. The results showed that the placement and assignment of educators and education personnel are regulated by the provisions of the Education Office because SMPN 18 Surabaya is a public school under the auspices of the Ministry of Education and Culture. The placement is carried out by considering the educational background, work experience, attitude, and appearance of prospective education personnel, as well as factors such as rank, domicile, and age. Obstacles in placement include discipline problems and less than optimal utilisation of educational resources. Meanwhile, obstacles in the assignment of education personnel include the low performance of teaching staff, lack of supervision, and the inability to improve educational resources.